Chemical nuclear data measurements and applications : proceedings of the international conference - Hurrell, M. Lyndsay (Institute of Civil Engineers, 1971)
Proceedings of an international conference held at the University of Kent at Canterbury on 20-22 September 1971.
Keywords: Radiochemistry -- Congresses.; Radioactive substances -- Congresses.; elektronické knihy; electronic books